PENGARUH PENUGASAN MAHASISWA GURU DI UNIT-UNIT USAHA TERHADAP MINAT BERWIRAUSAHA DITINJAU DARI PRESPEKTIF EKONOMI ISLAM (STUDI KASUS DI UNIT-UNIT USAHA PONDOK MODERN DARUSSALAM GONTOR KAMPUS 2) - Moch Adi Nur Ikhsan; Abdul Latif (Universitas Darussalam Gontor, 2021)
Entrepreneurship according to islamic view is one of the ways that a Muslim to obtain sustenance and happiness in the world and in the hereafter. Gontor teaches students and teachers entrepreneurial education through their educational facilities, namely assignments in the business units sector that are directly managed by students and teachers. This study aims to find out how much the influence of assignments in business units on the entrepreneurial interests of students, especially in Pondok Modern Darussalam Gontor Campus 2 and how much interest students teachers in entrepreneurship. This type of research is included in quantitative research, with data collection methods, observations and questionnaires. Took 60 samples using rosco method, and method to analyze researcher data using validity test, reliability test, normality test, heterokedastisity and using multiple linear regression coefience analyst method assisted with SPSS 21 analysis tool. The results of this study show that partial assignment has no effect on the entrepreneurial interests of teacher students. However, it simultaneously affects the entrepreneurial interests of teacher students with significant results of 0.000 < 0.05. All of these independent variables had an effect of 28.6% meaning that the other 71.4% were influenced by other factors not discussed in this study. While the entrepreneurial interest of students who are still relatively low because in the planning process is not appropriate so that it leads to prioritizing other interests such as leaving their duties in the cottage business units